Scientific And Technical Terminology as A Vocabulary of The Language of Communication of Specialists - Utkirova Mokhinur Uktam qizi (Zien Journals, 2022)
The scientific and technical style is a space for the functioning of scientific and technical communication. Within each functional style, some language features can be distinguished. The difference between languages is manifested not so much in the nomenclature of units, but in their compatibility, which is most often the result of a partial or complete mismatch in the volume of meanings of equivalent words and forms.
Keywords: scientific and technical style; term formation; term and terminology; special vocabulary